UJI KUALITAS SERUM SIMPANAN TERHADAP KADAR KOLESTEROL DALAM DARAH DI POLTEKKES KEMENKES KALTIM - Supri Hartini; Maria Eka Suryani (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
Clinical Chemistry Examination Guidelines stated several factors may affecting the stability of the specimen i.e. contaminant germs and chemicals, exposure to sunlight, the effects of temperature and metabolism of living cells such as blood cells. Blood specimens should be stored in the form of serum in a refrigerator at a temperature of 2-80 C. This study aimed to compare cholesterol levels of serum with no erythrocyte and with erythrocytes during storage for 3 and 9 days at 2-8ºC. This is an analytical survey to compare cholesterol levels in serum blood during storage. Data was analyzed using Independent Sample t-test. The result showed value p (0.410) is greater than α (0.05), so there is no correlation between serum with erythrocytes and with no erythrocytes in cholesterol at a temperature of 2-8 0C stored for 3 days and the p-value (0.162) is greater than α (0.05) then pat concluded that there was no influence of serum with erythrocytes and without erythrocytes to changes in cholesterol at a temperature of 2-8 0C during storage of 9 days